2012
DOI: 10.1016/j.ccr.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

MALT1 Small Molecule Inhibitors Specifically Suppress ABC-DLBCL In Vitro and In Vivo

Abstract: SUMMARY MALT1 cleavage activity is linked to the pathogenesis of activated B cell-like diffuse large B cell lymphoma (ABC-DLBCL), a chemoresistant form of DLBCL. We developed a MALT1 activity assay and identified chemically diverse MALT1 inhibitors. A selected lead compound, MI-2, featured direct binding to MALT1 and suppression of its protease function. MI-2 concentrated within human ABC-DLBCL cells and irreversibly inhibited cleavage of MALT1 substrates. This was accompanied by NF-κB reporter activity suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
269
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(273 citation statements)
references
References 52 publications
4
269
0
Order By: Relevance
“…35,36 However, recent advances in the design of small molecules and peptides and of nanotechnologies for drug-delivery approaches are opening new avenues in drug discovery to target transcription factors like Twist1. 37 In summary, this study provides insights into the relevance of Twist1 and regulated genes for the progression of poorly differentiated OSCC to metastasis and highlights their potential to be exploited as therapeutic targets for advanced OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 However, recent advances in the design of small molecules and peptides and of nanotechnologies for drug-delivery approaches are opening new avenues in drug discovery to target transcription factors like Twist1. 37 In summary, this study provides insights into the relevance of Twist1 and regulated genes for the progression of poorly differentiated OSCC to metastasis and highlights their potential to be exploited as therapeutic targets for advanced OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting aberrant activation of NF-κB and of MALT1 counteracts cell death and promotes unlimited growth (Shaffer et al, 2012). In return, ABC DLBCL cells develope a profound addiction to the CBM-NF-κB nexus and to MALT1 catalytic activity (Ferch et al, 2009;Fontan et al, 2012;Hailfinger et al, 2009;Nagel et al, 2012;Ngo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…His team showed that the antipsychotic compounds mepazine and thioridazine were also nanomolar-potent MALT1 inhibitors with in vivo efficacy in ABC-DLBCL. 8 Krappmann told SciBX that his team has since synthesized new inhibitors but also sees potential for thioridazine in the clinic. "We are in the process of working out a clinical repurposing trial with thioridazine because this drug is still available.…”
Section: Fermenting Strengthmentioning
confidence: 99%